Informal Channels for Conflict Resolution in Ibadan, Nigeria - Albert, Isaac Olawale; Awe, Tinu; Hérault, Georges; Omitoogun, Wuyi (IFRA-Nigeria, 2024)
Ibadan; informal justice; medias; Nigeria; informal networks; conflict solving